Effects of hypertonic solutions on two species of human intestinal parasites during fecal examination - Stefano, Vitoria C; Loiola, Saulo Hn; Dos Santos, Bianca M; Soares, Felipe A; Rosa, Stefany L; Suzuki, Celso Tn; Bresciani, Katia Ds [UNESP]; Sabadini, Edvaldo; Falcao, Alexandre X; Gomes, Jancarlo F (Taylor & Francis, 2023)
Aim: Ova and parasite examination by flotation requires hypertonic solutions, which can damage the egg and cyst membranes, leading to false negatives. The authors investigated the harmful effects of ZnSO4 and C12H22O11 solutions on the ova and parasite examination. Materials methods: The authors processed samples using the Three Fecal Test technique. Aliquots were floated in different pH levels, temperatures and solution densities. Results: Densities above 1.12 g/ml led structures to collapse after 6-10 min. pH neutralization of the ZnSO4 solution did not prevent the parasites from changing. Conclusion: All structures were altered when standard methods were performed. To delay collapse, the parasite floating under 5 °C is highly desirable.
Keywords: C12H22O11; hypertonic solution; parasitic infections; parasitology examination; ZnSO4